Endogenous network formation in local public goods: An experimental analysis - Ying Chen; Tom Lane; Stuart Macdonald (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
We experimentally explore public good production levels, and the endogenous formation of network structures to facilitate output sharing, among agents with heterogeneous production costs or valuations. Results corroborate the key theoretical insights of Kinateder & Merlino (2017) characterizing how agents form core-periphery networks. However, subjects often produce more and form denser networks than predicted, which sometimes reduces efficiency. There is some tendency for behaviour to converge towards the theoretical equilibrium over repeated play. Our results help us understand the emergence of the "law of the few" in real-world networks, and suggest it is driven by endogenous sorting of heterogeneous agents.
Keywords: C91; D85; H41; 330; Local public goods; Network formation; Experiment; Heterogeneity